2018
DOI: 10.2147/cmar.s183093
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy with bevacizumab and EGFR inhibitors for metastatic colorectal carcinoma: a national registry-based analysis

Abstract: Although inhibitors of vascular endothelial growth factor and inhibitors of epidermal growth factor receptor (EGFRi) are commonly used for the treatment of metastatic colorectal cancer (mCRC), the optimal sequencing of these agents is currently unclear. Methods: A national registry of targeted therapies was used to analyze baseline characteristics and outcomes of patients with mCRC and wild-type KRAS exon 2 status who received bevacizumab and EGFRi (cetuximab or panitumumab) as a part of first-and second-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…The therapy with targeted agents in the Czech Republic outside of clinical trials is reimbursed only in comprehensive cancer centers, and the registry has been estimated to provide data on approximately 95% of all patients treated with targeted therapy for mCRC in these centers. 8 There are 17 comprehensive cancer centers and all have contributed to the database. The contribution to the patient-based database was mandatory for regorafenib reimbursed by public health insurance.…”
Section: Patients Data Source and Inclusion Criteriamentioning
confidence: 99%
“…The therapy with targeted agents in the Czech Republic outside of clinical trials is reimbursed only in comprehensive cancer centers, and the registry has been estimated to provide data on approximately 95% of all patients treated with targeted therapy for mCRC in these centers. 8 There are 17 comprehensive cancer centers and all have contributed to the database. The contribution to the patient-based database was mandatory for regorafenib reimbursed by public health insurance.…”
Section: Patients Data Source and Inclusion Criteriamentioning
confidence: 99%
“…The comparison of our findings to other studies using real-world data from Europe is hampered regarding studies using certain criteria to select patients, e.g., if they excluded patients with early disease progression ( 11 , 12 ) or focused on patients with metachronous metastases ( 13 ). A study from the UK based on medical records, which included unselected patients with advanced CRC ( N = 714) similar to our approach, confirmed our findings.…”
Section: Discussionmentioning
confidence: 90%
“…So far, available studies using real-world data such as administrative claims are often based on data from the United States (8)(9)(10). To our knowledge, real-world evidence based on routinely collected data on utilization of biologics in CRC patients from Europe is limited to two studies from the Czech Republic using data from a specific drug registry, one study from the Netherlands using data from a regional cancer registry, and one from Italy based on five regional cancer registries (11)(12)(13)(14). Large claims or medical record databases from Europe have thus not been used for this purpose so far.…”
Section: Introductionmentioning
confidence: 99%
“…Aderka et al [ 143 ] hypothesized that the discrepancies monitored between these two trials, CALGB80405 and FIRE-3, can be due to the trial-specific sequence of chemotherapy plus targeted therapy. However, a recent study of Buchler et al [ 144 ] showed no differences in OS between cohorts treated with first-line bevacizumab and second-line EGFRi (cetuximab or panitumumab) vs. the reverse sequence. Another difference between the data presented by the CALGB80405 and FIRE-3 groups was observed for CMS1 and MSI tumors.…”
Section: Crc Molecular Subtypes In Therapy Outcome Predictionmentioning
confidence: 99%